Autisme dan Penanganan Kependidikannya - Imanuel Hitipeuw (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
Autism is an intellectual, social, emotional, language, and communication impairment emerging in infancy, which might continue to adulthood. It is a continuum. Since the characteristics of autism vary, it is reasonably difficult to determine what causes autism. What has been done so far is identifying the possible causes of autism based on the observable symptoms. Although there are a number of ways of handling autism, handling the language and social problems of autistic children is of immediate need to enable the children to be involved in their social environment. The results of diagnoses encourage parents to hold an expert shop.